NICHE RETAILING: SOUVENIR ATTRIBUTES AND PURCHASE INTENTIONS - Shanka, Tekle; Setiyati, Etsa; Taylor, Ruth (The journal of contemporary issues in business and government, 2008)
Retail tourism is a niche retail market of importance in Australia to both business and government with international students comprising a significant proportion of this market. A convenience sample of 216 international higher education (IHE) students at a West Australian university revealed that demographic characteristics showed statistically significant differences in authentic souvenir attributes and intention to purchase. Whilst female IHE students tend to buy arts, paintings or jewellery, IHE students from the Asian region tend to buy collectables or accessories. Older IHE students are more likely to purchase authentic souvenirs as gifts for other people. Overall, Australian souvenirs made in Australia were considered as being of high quality, expensive, authentic and prestigious compared with Australian souvenirs made elsewhere. Additionally, factor analysis showed that features influencing souvenir purchases could be grouped according to the four attributes of innovativeness, portability, symbolism and popularity.